The Effect of Avocado Consumption on Increasing Hemoglobin Levels in Pregnant Women at PMB Nellyana Working Area of the Sitinjo Sidikalang Health Center in 2023 - Eka Permatasari Purba; Raskhita Irena Debora Tarigan (Sean Institute, 2025)
Anemia in pregnancy is a national problem reflecting well being social economic of public. Anemia in pregnancy potentially dangereous for mother and fetus because defisiensi Hb in blood can cause serious complication.Treatment pharmacology for treat anemia with consuming Fe tablet supplements and non- pharmacological with consuming fruit juice avocado. Avocado is fruit that is rich in vitamin A which plays a role in formation cell blood red through the interaction with Fe minerals so that prevent anemia occurs. This is Quantitative with design quasi experiment with design Two Group post test control design. Sample use purposive sampling technique with amount sample 16 respondents use 2 groups treatment and group control. Research statistical analysis this using the paired sample T- test , based on paired t- test Hb levels in respondents before and after given avocado juice obtained value Sig. (2-tailed) i.e. 0.00 or more small of p <0.05, while for respondents who do not given avocado obtained value Sig. (2-tailed) before and after i.e. 0.351 or more big from p>0.05. Based on results the could concluded that there is influence fruit juice _ avocado significant on the increase respondent 's Hb level compared with respondents who do not given avocado.